Pro Power BI Desktop - Aspin, Adam (Apress, 2018)
Deliver eye-catching Business Intelligence with Microsoft Power BI Desktop. This new edition has been updated to cover all the latest features, including combo charts, Cartesian charts, trend lines, use of gauges, and more. Also covered are Top-N features, the ability to bin data into groupings and chart the groupings, and new techniques for detecting and handling outlier data points. You can take data from virtually any source and use it to produce stunning dashboards and compelling reports that will seize your audience's attention. Slice and dice the data with remarkable ease and then add metrics and KPIs to project the insights that create your competitive advantage. Make raw data into clear, accurate, and interactive information with Microsoft's free self-service business intelligence tool. Pro Power BI Desktop shows you how to choose from a wide range of built-in and third-party visualization types so that your message is always enhanced. You'll be able to deliver those results on the PC, tablets, and smartphones, as well as share results via the cloud. This book helps you save time by preparing the underlying data correctly without needing an IT department to prepare it for you. What You'll Learn: Deliver attention-grabbing information, turning data into insight Mash up data from multiple sources into a cleansed and coherent data model Create dashboards that help in monitoring key performance indicators of your business Build interdependent charts, maps, and tables to deliver visually stunning information Share business intelligence in the cloud without involving IT Deliver visually stunning and interactive charts, maps, and tables Find new insights as you chop and tweak your data as never before Adapt delivery to mobile devices such as phones and tablets.